Efecto del porcentaje de sustitución de la harina de trigo por extracto de posos de café gastado (SCG) en la actividad antioxidante, características sensoriales y color de galletas dulces - Mayorga Yuntul, Francisco André (2019)
The present study search to use coffee waste in bakery product applications, as an effective way to reduce waste and minimize the environmental impact generated. The objective of this work was the determination of the effect of extracts of spent coffee grounds (SCG) on the antioxidant activity, color and sensory characteristics of sweet cookies, for this the melanoidins were extracted by ethanol precipitation, then it was incorporated into the cookie formulation (amounts of 1, 4 and 7% w / w related to the flour content) baked at a temperature of 140 ° C for 15 minutes and finally stored in airtight bags. To compare the effect of SCG substitution (1, 4 and 7%) on the color parameters of sweet cookies, Variance Analysis (ANOVA) was used by means of Statgraphics software finding that SCG substitutions are significant (p <0.05). The CATA method and the mapping by preference (Correspondence Analysis, Principal Component and Cluster Analysis), evaluated 4 treatments (0, 1, 4 and 7% w / w) found that the best acceptability is achieved when the cookie is formulated with 4 % w / w replacement and a corresponding antioxidant activity even IC50 of 7.70 mg / ml. it was obtained an increase in antioxidant activity (AOA) of up to a maximum of 64% was obtained for a replacement of 7% w / w without affecting the properties of the cookie (taste, texture and general acceptability).